What does exercise-based assessment really mean? - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2008)
My commentary addresses Lance’s (2008) recommendation to reorient assessment center (AC) practice away from dimensions toward exercise-based assessment. As exercise-based assessment is dealt with only in general terms in Lance’s article, I aim to delineate what exercise-based assessment really means. Two points are made. First, I arguethattakingdimensionsawayfromACs does not mean that assessee behavior is no longer determined by latent traits because behavior is inherently trait determined. Second, I elaborate on the practical and research implications of exercise-based assessment because these implications are underdeveloped in Lance.